Estratégias para incremento das atividades de celulases e xilanases por penicillium echinulatum SIM29 em cultivo submerso - Reis, Laísa dos (My University, 2017)
Cellulases and xylanases are enzymes with ability to hydrolyze cellulose and hemicellulose, respectively, from plant biomass, releasing fermentable sugars that can be converted into various biotechnological products. Among the microorganisms that produce these enzymes, the strain S1M29 of Penicillium echinulatum distinguishes. Knowledge about physiology of the microorganism is very important for reaching strategies that lead to increases in the enzymatic activities and thus, reduce the costs of enzymes production. Among these strategies, there are the use of low cost lignocellulosic substrates, the reuse of the mycelial mass and the use of fed-batch cultivation (FBC). Regarding the studies on submerged cultures with P. echinulatum, the medium of this work was composed of hemicellulosic carbon source, sucrose, salt solution, Tween 80®, wheat bran and soybean meal. Erlenmeyer flasks were used to evaluate the effect of cellulose concentration on mycelial growth and enzymatic production, also to select lignocellulosic materials for their ability to replace 50% of the cellulose present in the culture medium and to evaluate the possibility of reuse of mycelial mass. To produce cellulases and xylanases in a bench-bioreactor during the FBC, an automatic microcrystalline cellulose addition system was developed. The enzyme obtained were evaluated for their ability of hydrolysis of elephant grass and sugarcane bagasse. The increase of the cellulose concentration resulted in a higher level of biomass of P. echinulatum, however, under these conditions, lower activities of cellulases and xylanases were obtained. Orange pomace and pre-treated elephant grass can substitute commercial cellulose by 50% and enable greater production of β-glucosidases and exoglucanases. The reuse of fungal biomass has increased the enzymatic activities and can be employed for at least five production cycles. The automatic cellulose feeder type conveyor shaft proved to be a practical and efficient system for adding cellulose during the FBC and the most appropriate cellulose feed rate was 0.26 ± 0.02 g/L/h. Activities of FPA (14 IU/mL), endoglucanases (116 IU/mL), xylanases (1032 IU/mL), β-glucosidases (4.7 IU/mL) and exoglucanases (10.8 IU/mL) were obtained during FBC with cellulose equivalent to 60 g/L and feed during 192 hours of cultivation. The enzymatic complex of P. echinulatum obtained were more efficient in the hydrolysis of elephant grass and sugarcane bagasse in natura when compared to the commercial enzyme Celluclast 1.5L® from Novozymes. These results contribute to the economical production of enzymes by P. echinulatum in submerged culture.
As celulases e xilanases são enzimas que apresentam a capacidade de hidrolisar a celulose e a hemicelulose, respectivamente, da biomassa vegetal, liberando açúcares fermentescíveis que podem ser convertidos em diversos produtos biotecnológicos. Entre os microrganismos produtores destas enzimas, destaca-se a linhagem S1M29 de Penicillium echinulatum. O conhecimento da fisiologia do microrganismo é muito importante para alcançar estratégias que permitam obter aumentos nas atividades enzimáticas e assim, reduzir os custos de produção de enzimas. Entre estas estratégias, está o emprego de substratos lignocelulósicos de baixo custo, a reutilização da massa micelial e o emprego do regime descontínuo alimentado (RDA). Para os estudos em cultivos submersos com P. echinulatum, o meio de cultivo deste trabalho foi composto pela fonte de carbono hemicelulósica, sacarose, solução de sais, Tween 80®, farelo trigo e farelo de soja. Frascos Erlenmeyer foram empregados para avaliar o efeito da concentração de celulose no crescimento micelial e na produção enzimática, também para selecionar materiais lignocelulósicos quanto à capacidade de substituir 50% da celulose presente no meio de cultivo e avaliar a possibilidade de reutilização de massa micelial. Para a produção de celulases e xilanases em biorreator de bancada em RDA, um sistema automático de adição da celulose microcristalina foi desenvolvido. As enzimas obtidas foram avaliadas quanto à capacidade de hidrólise de capim-elefante (CE) e bagaço de cana-de-açúcar (BCA). O aumento da concentração de celulose resultou em maior biomassa de P. echinulatum, entretanto, nessas condições, menores atividades de celulases e xilanases foram obtidas. O bagaço de laranja e o capim-elefante pré-tratado podem substituir em 50% a celulose comercial e possibilitaram maior produção de β-glicosidases e exoglicanases. A reutilização da biomassa fúngica aumentou as atividades enzimáticas e pode ser empregada por pelos menos cinco ciclos de produção. O alimentador automático de celulose do tipo rosca transportadora mostrou-se um sistema prático e eficiente para adicionar a celulose durante o RDA e a velocidade de alimentação de celulose mais apropriada foi 0,26±0,02 g/L/h. Atividades de FPA (14 UI/mL), endoglicanases (116 UI/mL), xilanases (1032 UI/mL), βglicosidases (4,7 UI/mL) e exoglicanases (10,8 UI/mL) foram obtidas durante o RDA com celulose equivalente a 60 g/L e alimentação durante 192 horas de cultivo. O complexo enzimático de P. echinulatum foi mais eficiente na hidrólise de CE e BCA in natura quando comparados à enzima comercial Celluclast 1.5L® da Novozymes. Estes resultados contribuem com a produção econômica de enzimas por P. echinulatum em cultivo submerso.
Keywords: Penicillium; Celulose; Celulase; Xilanases; Enzimas; Micro-organismos; Cellulose; Cellulase; Xylanases; Enzymes; Microorganisms